MANAJEMEN BUDAYA AKADEMIK SEKOLAH DASAR MUHAMMADIYAH AL-MUJAHIDIN WONOSARI TAHUN PELAJARAN 2013/2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
This research aimed at investigating academic culture management at Muhammadiyah Al-Mujahidin Elementary School in Wonosari which was realized, internalized, and actualized at Muhammadiyah Al-Mujahidin Elementary School in Wonosari.This research was a descriptive research which adopted a qualitative approach with a case study design.This research focused only on some phenomena which were deeply internalized and neglected some other phenomena. Research data were obtained by conducting direct observation and documentation study.The conclusions of the research were: 1) academic culture management at Muhammadiyah Al-Mujadidin Elementary School generally ran well which was proved from the academic achievements, 2) the function of academic culture planning ranged from intracurricular to extracurricular programmes in which academic culture was found, 3) organizing function consisted of scheduling and delegating jobs based on organization structure in order that organization ran effectively and efficiently, 4) executing function dealt with the execution of intracurricular and extracurricular activities either inside or outside school, 5) supervising, evaluating and controlling activities were conducted in order to guarantee a never-ending service quality, 6) academic culture management played an important role in enhancing academic achievement, 7) academic culture strategy eventually gave a real contribution to the academic achievement of the school.